PENGARUH PROFITABILITAS, LIKUIDITAS, TANGIBILITY, NON-DEBT TAX SHIELD, DAN PERTUMBUHAN PENJUALAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2012 - Indah Nurhayati, 10.05.52.0125; Indarti, M.G. Kentris (Students Journal of Accounting and Banking, 2014)
This study is a study that examines the effect of profitability, liquidity, tangibility, Non-Debt Tax Shield, and Sales Growth to Capital Structure Manufacturing Company listed on the Indonesia Stock Exchange Period 2010-2012. This study also uses control variables Firm Size is measured by LN (total assets). The sample used in this study are listed Manufacturing Company in Indonesia Stock Exchange Period 2010-2012. Pengambilan sampel method used in this study was purposive sampling. The sample used by 49 companies. Data analysis tool used is multiple linear regression Ordinary Least Squares (OLS). These results indicate that profitability and liquidity variables significant negative effect on the capital structure, variable tangibility and non-debt tax shield is not significant negative effect on capital structure, variable sales growth effect is not significant and positive. This study also shows that the variable Firm size as control variables significant positive effect on capital structure.Keywords: Capital Structure, Profitability, Liquidity, tangibility, Non-Debt Tax Shield, and Sales GrowthÂ